2004
DOI: 10.1111/j.1469-7610.2004.00320.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal personality and infants’ neural and visual responsivity to facial expressions of emotion

Abstract: To the extent that these variations in maternal disposition reflect variations in their expression of positive facial expressions, these results suggest that the emotional environment experienced by infants contributes to the development of their responses to facial expressions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
191
6
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(230 citation statements)
references
References 72 publications
26
191
6
6
Order By: Relevance
“…Only in the right hemisphere and only for original stimuli did the Nc differ between gaze directions [F(1,21) = 4.4, P = 0.048, η 2 = 0.17]; direct gaze elicited greater Nc than averted gaze [t(21) = −2.14, P = 0.044, r = 0.42, direct −8.27 ± 2.95 μV, averted −0.25 ± 3.65 μV]. Note that although this effect was only significant in the right hemisphere, which is sometimes observed in studies of face processing (50,51), the ERPs showed a similar modulation in the left hemisphere and the overall topography of the effect was similar to experiment 1 ( Fig. 4; see Fig.…”
Section: Experiments 2: Gaze Processingmentioning
confidence: 74%
“…Only in the right hemisphere and only for original stimuli did the Nc differ between gaze directions [F(1,21) = 4.4, P = 0.048, η 2 = 0.17]; direct gaze elicited greater Nc than averted gaze [t(21) = −2.14, P = 0.044, r = 0.42, direct −8.27 ± 2.95 μV, averted −0.25 ± 3.65 μV]. Note that although this effect was only significant in the right hemisphere, which is sometimes observed in studies of face processing (50,51), the ERPs showed a similar modulation in the left hemisphere and the overall topography of the effect was similar to experiment 1 ( Fig. 4; see Fig.…”
Section: Experiments 2: Gaze Processingmentioning
confidence: 74%
“…Converging evidence comes from infants' ERPs. Nelson andde Haan (1996) andde Haan et al (2004) found that the Nc in 7-month-old infants' ERPs was greater in amplitude to fearful than to happy faces. Recall from section 1a that the Nc is thought to reflect infants' allocation of attention.…”
Section: A the Negativity Bias In Attention To Emotionsmentioning
confidence: 99%
“…It is assumed that the ability to recognize facial emotions is in part due to a biological readiness, but environmental factors are of importance as well (de Haan et al, 2004;Herba and Phillips, 2004). However, little is known about the influence of psychiatric disorders during childhood or adolescence on the development of this function.…”
Section: Introductionmentioning
confidence: 99%